Innovation in the Management of ZIS (Zakat, Infaq and Shadaqah) in the Zakat Collecting Unit (UPZ) IAIN Madura - Nur Asnawi; Fatimatuz Zahroh; Meldona Meldona (International Journal of Management Research and Economics, 2024)
The Zakat Management Unit (UPZ) of IAIN Madura is part of the National Amil Zakat Agency (BAZNAS) of East Java which has implemented excellent programs in increasing rapid development over the last 5 years effectively and sustainably in the social sector, especially in the management of zakat, infaq, and shadaqah (ZIS) funds. UPZ IAIN Madura conducts data collection, and mapping of muzakki (donors) and mustahiq (beneficiaries) to ensure that the distribution of ZIS funds is on target through superior programs in the form of social assistance, education, health, economy, and other basic needs. The research method carried out by this study uses a descriptive qualitative approach with field research techniques through direct observation and interviews with 10 informants, namely the management of UPZ IAIN Madura and several mustahiq. The triangulation carried out is in the form of triangulation of data, theories, and methods. The results of the study show that the management of ZIS at UPZ IAIN Madura is implemented through six flagship programs, namely UPZ Sehat, UPZ Peduli, UPZ Serving, UPZ Sejahtera, UPZ Smart, and UPZ Clean. Innovation in ZIS management is manifested in the form of the use of information technology, applications, and transfer systems in flagship programs, for example, the use of Qris in UPZ Sejahtera, the application of scholarship information technology in UPZ Smart, the use of digital reporting applications in the UPZ Peduli program, health service collaboration in UPZ Sehat, and waste management as a source of funding for social programs in UPZ Bersih.